Participatory Governance in Multicentric Systems - Ramjit, Dana-Marie (Department of Public Administration, Parahyangan Catholic University, 2026)
Contemporary public administration has shifted from hierarchical, state-centric models toward multilevel and multicentric governance, in which authority is dispersed across governments, markets, civil society, and citizens. While citizen participation and co-production are central to legitimacy, inclusiveness, and public service performance, structural inequalities, power asymmetries, and coordination challenges frequently constrain meaningful influence, producing engagement that is often symbolic rather than substantive. Drawing on postinternationalist theory, this paper conceptualizes governance as a turbulent, fragmented, and overlapping system characterized by distant proximities, where interdependence coexists with unequal access to power. It examines how these dynamics shape citizen participation, highlighting how structural, relational, and digital inequalities mediate the translation of presence into influence. The analysis integrates empirical examples from diverse governance contexts to illustrate the risks of co-optation and agenda capture and identifies drivers and barriers of substantive participation. Practically, the paper offers guidance for public managers, emphasizing heterarchical leadership, adaptive coordination, and the design of participatory mechanisms that ensure inclusiveness, accountability, and measurable public value. By linking theoretical insights on turbulence, fragmegration, and distant proximities with strategies for public administration, the paper reframes citizen engagement not as a bureaucratic add-on, but as a structurally conditioned determinant of legitimacy, innovation, and effectiveness in complex governance systems.